Insights into the epigenomic landscape of the human malaria vector Anopheles gambiae - Gómez-Díaz, Elena; Rivero, Ana; Chandre, Fabrice; Corces, Victor G. (Frontiers in Genetics, 2014)
The epigenome of the human malaria vector Anopheles gambiae was characterized in midgut cells by mapping the distribution and levels of two post-translational histone modifications, H3K27ac and H3K27me3. These histone profiles were then correlated with levels of gene expression obtained by RNA-seq. Analysis of the transcriptome of A. gambiae midguts and salivary glands led to the discovery of 13,898 new transcripts not present in the most recent genome assembly. A subset of these transcripts is differentially expressed between midgut and salivary glands. The enrichment profiles of H3K27ac and H3K27me3 are mutually exclusive and associate with high and low levels of transcription, respectively. This distribution agrees with previous findings in Drosophila showing association of these two histone modifications with either active or inactive transcriptional states, including Polycomb-associated domains in silenced genes. This study provides a mosquito epigenomics platform for future comparative studies in other mosquito species, opening future investigations into the role of epigenetic processes in vector-borne systems of medical and economic importance.